Osteopetrosis in a neonatal donkey. Issue 10 (27th September 2016) - Williamson, AJ; Stent, AW; Milne, M; Walmsley, EA
Abstract : Osteopetrosis is a rare disorder characterised by a defect in osteoclastic bone resorption. This report describes osteopetrosis in a neonatal donkey that suffered a displaced tibial fracture. Radiographic examination identified generalised reduction in medullary cavity size, thickened mid‐diaphyseal cortices and conical metaphyseal bone extending toward the mid‐diaphysis of long bones. Postmortem examination identified additional fractures and brittle bones. Histologically, osteoclasts were absent in multiple bone sections. Diaphyseal cortices consisted of concentric bone lamellae with marrow tissue infiltration. Large wedges of secondary spongiosa extended from the metaphyseal growth plate. Clinical and histopathological features were similar to an osteoclast‐deficient, autosomal recessive form of osteopetrosis in humans.